Pengaruh Konsentrasi Aktivator Asam Klorida (HCL) Terhadap Kapasitas Adsorpsi Arang Aktif Kulit Durian (Durio Zibethinus) pada Zat Warna Methanil Yellow - Supiati, Supiati; Yudi, Muh.; Chadijah, St (Al-Kimia, 2013)
Durian’s peel a waste which usually burned, stacked or discarded, which are unfavorable to environment. This condition motivates author to produce value-added products from the durian peel, such as activated carbon, as well as solving some environmental problems. This research aims to know the influence to use variation of concentration of activator HCl whice produces the optimum adsorption capacity from charcoal active of durian’s peel to the substance color of methanil yellow. Active carbon which is used in this research comes from durian’s peel which granular types with standard -100+40 mesh. Carbon is activated by physics in furnace with 400°C heat during 2 hours and is activated by chemistry with submerged of HCI 1M, 2M, 3M, 4M and 5M during 24 hours. The result of this research shows that optimum concentration in HCI 1M with adsorption capacity from charcoal active of durian’s peel is as large as 0,5350 mg/g. Whereas knowing the influence of activator is used tabulation method by statistically, where we can get F Hitung 0,004 is smaller from F Tabel 10,127. It explains that H0 is accepted to reject H1. Therefore, it can conclude that there is not significant influence to use variation of concentration of activator HCl to adsorption capacity of charcoal active from durian’s peel in substance methanil yellow.